Updated List of Light-Sensitive Oral Medications. (December 2020) - Perkins, Scott; Evans, Adam; King, Allison
The Campbell University Drug Information Center supports health professionals by providing responses to drug-related inquiries. An inquiry was received by the Drug Information Center for a comprehensive list of oral solutions which should be protected from light. In investigating this request for information, a list of light-sensitive oral prescription drug products published in Hospital Pharmacy in 2009 was identified. This discovery highlighted the need for both an updated list and one which distinguished oral solid products and oral liquid products. The purpose of this project was to update the previously published list and to distinguish between oral solid and liquid dosage forms. The process of updating this list entailed several professional resources. A list of all oral products was obtained and then sorted to clearly identify which products were available in oral solid dosage form only, oral liquid dosage form only, and both dosage forms. Once delineated, the product labels for each medication were scoured for language indicating the product is light sensitive.